A hardware and environment-agnostic smart home architecture with containerized on-the-fly service offloading. (June 2021) - Ozmen, Huseyin Anil; Isik, Sinan; Ersoy, Cem
Abstract: The Fog-based Home Automation Platform (FOGHA) is a novel Fog-based smart home platform that utilizes real-time containerized service deployment and task-offloading over its computing nodes. Fog is the middle computing layer that is physically near to the Things layer (connected appliances) and is composed of multiple Fog nodes that are orchestrated in a distributed manner. The architecture supports intra-Fog and inter-layer task offloading mechanisms via the real-time deployment of containerized services. The delay-sensitive services are mostly performed among Fog nodes, whereas the resource-demanding tasks are offloaded to the Cloud nodes. FOGHA utilizes software services as Docker containers, which is a novel approach for resource-scarce Fog nodes compared to existing automation platforms. Our experiments proved that resource-demanding tasks such as face recognition could also be collectively performed within the Fog layer, revealing that Fog layer nodes can provide the Cloud layer's computational power and service variety. Graphical abstract: Highlights: Moving services from Cloud to Fog with geographically distributed low profile servers. Containerization utilized in real time service deployment and task offloading. Dynamic and adaptive intra-Fog and inter-layer task offloading shown to be effective.